Modernization and citizenship: The Mexico City Experience, 1870-1930 - Bracamonte Allaín, Jorge (1997)
The story that follows is an approximation to the experience of appropriation of modernity by different social groups in Mexico City between the years of 1870 and 1930. This experience can be analyzed from two variables: modernization of the city and the development of citizenship. In the first case, modernization leads us to the study of the rigid social structures that contextualize -based on criteria of inequality- the processes of urbanization and suburbanization of the city. In the second case, citizenship leads us to the subjective experience of men and women who, in their struggle for equality, seek to transcend the borders of differences marked by the social structure.